Does bone marrow aspirate help enhance the integration of gamma irradiated allograft bone? - Thong, Fu Yuen; Mansor, Azura; Ramalingam, Saravana; Yusof, Norimah (Springer, 2020)
Bone allografts donated by other individuals offer a viable alternative to autograft. Risks of disease transmission are overcome by sterilizing the bone; unfortunately sterilization methods generally affect bone functional properties including osteogenic potential and biomechanical integrity. This study aimed to determine any enhancement effect when gamma sterilised allografts was impregnated with autologous bone marrow in improving the rate and quality of integration in metaphyseal-tibial defects of rabbits. Almost all subjects showed 50% of the defect being covered by new bones by the third week and smaller residual defect size in the treated group at the fifth week. Hounsfield units at the defect site showed increasing healing in all samples, with the treated group having an apparent advantage although insignificant (p > 0.05). In the histopathological score evaluating healing over cortical and cancellous bone at the fracture site showed only slight variations between the groups (p > 0.05). Therefore no enhanced healing by the autologous bone marrow was observed when added to the bone allografts in treating the unicortical defects. © 2020, Springer Nature B.V.